Exposure to isomers of per- and polyfluoroalkyl substances increases the risk of diabetes and impairs glucose-homeostasis in Chinese adults: Isomers of C8 health project. (September 2021) - Zeeshan, Mohammed; Zhang, Yun-Ting; Yu, Shu; Huang, Wen-Zhong; Zhou, Yang; Vinothkumar, Rajamanickam; Chu, Chu; Li, Qing-Qing; Wu, Qi-Zhen; Ye, Wan-Lin; Zhou, Peien; Dong, Pengxin; et al.
Abstract: Per- and polyfluoroalkyl substances (PFAS) exposure has been linked to diabetes, but evidence on the association of isomers of PFAS with type 2 diabetes (T2D) remains scant. This population based cross-sectional study aimed to investigate associations between serum PFAS isomers, glucose-homeostasis markers and T2D, adjusted for multiple potential confounders. We used data from "Isomers of C8 Health Project in China" from July 2015 to October 2016. A total of 10 PFAS including isomers of PFOS and PFOA were measured in serum of 1045 Chinese adults. Fasting blood glucose, fasting insulin, homeostasis model of insulin (HOMA-IR) and beta cell function (HOMA-β) were considered as markers of glucose-homeostasis. We found significant positive associations between serum PFAS isomers and glucose-homeostasis markers, namely, fasting blood glucose, fasting insulin and HOMA-IR. Per log-unit increase in branched (br)-PFOS concentration was associated with increased fasting blood glucose (β = 0.25, 95% CI: 0.18, 0.33), fasting insulin (β = 2.19, 95% CI: 1.44, 2.93) and HOMA-IR (β = 0.69, 95% CI: 0.50, 0.89). As compared to br-PFOS, linear (n)-PFOS and -PFOA showed lesser significant associations with glucose-homeostasis makers. Further, exposure to all PFAS including isomeric PFOS, PFOA and PFHxS increased the risk of T2D with br-PFOS exhibiting the highest risk (OR = 5.41, 95% CI: 3.68–7.96). The associations were stronger among women than men. In conclusion, chronic exposure to PFAS isomers was associated with impaired glucose-homeostasis and may increase the prevalence of T2D in Chinese adults. Given the ubiquity of PFAS in the environment and the public health burden of T2D, future studies are warranted to corroborate the findings. Graphical abstract: Image 1 Highlights: Environmental exposure may play a role in pathogenesis of type 2 diabetes (T2D). Serum concentrations of PFAS isomers altered glucose homeostasis in Chinese. Exposure to PFAS isomers were also associated with an increased risk of T2D in adults. The associations were stronger for branched PFOS than linear PFOS. The associations were stronger in women than men.